2010
DOI: 10.1093/brain/awq229
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation during cognitive planning in twins discordant or concordant for obsessive-compulsive symptoms

Abstract: Neuroimaging studies have indicated abnormalities in cortico-striatal-thalamo-cortical circuits in patients with obsessive–compulsive disorder compared with controls. However, there are inconsistencies between studies regarding the exact set of brain structures involved and the direction of anatomical and functional changes. These inconsistencies may reflect the differential impact of environmental and genetic risk factors for obsessive–compulsive disorder on different parts of the brain. To distinguish betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 106 publications
1
34
0
Order By: Relevance
“…77,78,85 In addition, functional MRI and positron emission tomography studies of OCD patients have shown that stimulus presentation activates the orbitofrontal cortex, dorsolateral prefrontal cortex, anterior cingulate cortex, and basal ganglia structures. 2,14,23,55,70,76 In line with these findings, successful treatment of OCD by pharmacological, behavioral, and neurosurgical methods reduces activity in this circuit. 9,33,63,80,84 …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…77,78,85 In addition, functional MRI and positron emission tomography studies of OCD patients have shown that stimulus presentation activates the orbitofrontal cortex, dorsolateral prefrontal cortex, anterior cingulate cortex, and basal ganglia structures. 2,14,23,55,70,76 In line with these findings, successful treatment of OCD by pharmacological, behavioral, and neurosurgical methods reduces activity in this circuit. 9,33,63,80,84 …”
Section: Discussionmentioning
confidence: 70%
“…12 Because of its role in regulation of emotions, motivation, and behavioral planning, which has been linked to compulsions, obsessions, and intrusive thoughts, the orbitofrontal cortex influences the presentation of psychiatric symptoms. 12,23 Similarly important, the anterior cingulate cortex probably triggers repetitive behaviors through its involvement in conflict monitoring. 11,12,22,40 The ventromedial prefrontal cortex and the dorsolateral prefrontal cortex have also been associated with psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, distinct OCD endophenotypes (e.g., washers, hoarders, checkers) as well as different types of risk (genetic risk versus environmental) were reported to be associated with specific brain activation patterns (Mataix-Cols et al 2004;den Braber et al 2010). By not differentiating the response in terms of OCD symptomatic profile and genetic risk, the present results were averaged across what may have been a compound of distinct responses.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Rotge et al (2008), on a quantitative voxel-based meta-analysis of the functional studies (fMRI and PET), and using a symptom provocation paradigm, reported evidence for the hyperactivation of cortico-striatopallido-thalamo-cortical circuits, but also other regions such as the superior temporal gyrus, precuneus, and dorsolateral prefrontal cortex. On a more extended and inclusive narrative review (all types of functional studies), Del Casale et al (2011), reported a complex picture involving dysfunction Fig. 1 a Regions where OCD patients, when compared with healthy controls, showed increased activation for the defensive system condition; b Regions where participants from the healthy controls group, when compared with OCD, showed increased activation in the appetitive system condition (mainly hyper activation) of frontal, parietal and temporal cortices, basal ganglia, amygdala, cingulate cortex, and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…For example, meta-analyses have shown that patients with OCD have reduced gray matter density in the dorsolateral prefrontal cortex (DLPFC) and OFC and reduced volume of the anterior cingulate cortex (ACC) and OFC (Rotge et al 2009; Rotge et al 2010a; Szeszko et al 1999). In addition, fMRI and PET studies of OCD patients have shown that stimulus presentation activates the OFC, DLPFC, ACC, and basal ganglia (Adler et al 2000; Braber et al 2010; Breiter et al 1996; McGuire et al 1994; Rauch et al 1994; Rotge et al 2008). Notably, successful treatment of OCD by pharmacologic, behavioral, and neurosurgical methods reduces activity in this circuit (Baxter et al 1992; Haber and Brucker 2009; Perani et al 1995; Schwartz et al 1996; Swedo et al 1992).…”
Section: Discussionmentioning
confidence: 99%